Reduction of proteinuria in patients with diabetes kidney disease and dysautonomia through measures aimed at controlling supine hypertension - Palhares Aversa Santos, Guilherme [UNESP]; Inomata Cardoso da Silva, Douglas [UNESP]; Burgugi Banin, Vanessa [UNESP]; Garcia Zanati Bazan, Silméia [UNESP]; Barretti, Pasqual [UNESP]; Jorge da Silva Franco, Roberto [UNESP]; Martin, Luis Cuadrado [UNESP] (Taylor & Francis, 2022)
In diabetes kidney disease (DKD), orthostatic hypotension and supine hypertension often coexist, which, when uncontrolled, contributes to the progression of proteinuria and renal dysfunction. Chronotherapy and elevation of the head of the bed during sleep are feasible clinical measures and could contribute to the control of supine hypertension and proteinuria in this group of patients. This study consists of a series of cases, in which nine consecutive patients with DKD, dysautonomia and supine hypertension (intervention group) were instructed to use chronotherapy and inclination of the head of the bed in six degrees during sleep. These patients were compared with a historical control group. The primary outcome was proteinuria behavior. The intervention group had a significant drop in proteinuria levels, while there was an increase in proteinuria in the control group (variation in the proteinuria/creatininuria index in an isolated sample from the intervention group: −6.60 ± 3.90 g/g; variation in the group control: +1.70 ± 7.10 g/g, p = 0.008). Chronotherapy and six-degree inclination of the head of the bed during sleep were associated with a significant decrease in proteinuria in patients in the intervention group, with conversion of nephrotic into non-nephrotic proteinuria in most of these patients.
Keywords: Chronic kidney disease; chronotherapy; diabetic nephropathy; hypertension; proteinuria; supine hypertension